Seasonal Incidence of Wood Destroying Subterranean Termites - Chatterjee, P. N.; Sen-Sarma, P. K. (Indian Forester, 1962)
Preliminary results of studies on the seasonal incidence of wood destroying subterranean termites carried out at Dehra Dun in the New Forest Insectary Garden of Forest Research Institute are given. The highest incidence of termites occurs from the middle of August to the end of September in Dehra Dun; The relation of rainfall with incidence of termites appears somewhat inverse.